P2.014 Development and Analytical Performance of New CT/NG Nucleic Acid Amplified Test (NAAT). (13th July 2013) - Weir, F A; Foxall, P; Alugupally, S; Satya, M; Ho, K; Lee, A
Abstract : Background: Moderately complex NAATs that can provide fast, actionable results could reduce the burden of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections. The Xpert ® CT/NG Assay is a recently FDA-cleared, moderately complex assay for the detection of CT and NG in patient collected vaginal swabs, endocervical swabs, and male and female urines with a turnaround time of 87 minutes. Methods: Primers and probes were designed against specific CT and NG candidate genomic targets and screened for exclusivity with genomic DNA extracted from non-trachomal Chlamydia/Chlamydophila and non-gonococcal Neisseria species. For inclusivity, genomic DNA extracted from the 15 CT serovars and 230 geographically diverse NG strains was used. A multiplex assay, running on the GeneXpert platform, was designed to detect one CT target, two independent unique NG targets and two control targets. Analytical reactivity and specificity were determined by testing whole organisms. Analytical sensitivity was determined using titered, purified CT elementary bodies and cultured NG cells. Results: The Xpert CT/NG assay detects all CT serovars, new variant CT, and 48 geographically diverse NG strains. The CT primers and probes do not cross-react with DNA or RNA from non-trachomal species. All non-gonococcal Neisseria species yielded negative results, including N. mucosa and N. cinerea, because both NG targets must be PCR positive for a "NG DETECTED" result. The LoDs for the Xpert CT/NG Assay for CT serovar D in male urine and vaginal swab matrix respectively were 75 and 84 Eb/mL; for CT serovar H, LoDs were 134 and 161 Eb/mL. In both matrices, the LoD for two NG strains was approximately 2 cfu/mL. Conclusion: The Xpert CT/NG assay is highly specific and sensitive. The ease of use and fast time to result could lead to reduced time to treatment of CT and NG infections.